Photosynthetic organisms and water quality in Amazonian rivers, case study Yacuambi, Zamora Chinchipe - Cartuche, Alonso; Aguirre, Nikolay; Yaguana, Roberth; Bustillos, Roberto; Alvarado, Vinicio; Encalada, Max; Balcazar, Josselyn (ACI Avances en Ciencias e Ingenierías, 2025)
Mining and livestock activities in the Yacuambi canton significantly alter the ecological conditions of aquatic bodies, particularly rivers and water sources used for human consumption. This study evaluated water quality using methods based on bioindicators, specifically phytoplankton, as a complementary approach to physicochemical assessments. Phytoplankton play a crucial role in the structure and primary production of aquatic ecosystems; therefore, analyzing their composition and structure serves as a biological indicator of water quality. In situ water samples were collected for both physicochemical analysis (pH, dissolved oxygen, conductivity, total dissolved solids, temperature, nitrates, and phosphates) and biological analysis (diatoms). In the laboratory, microscopy and quantification of phytoplanktonic cells were conducted, enabling the application of an index to determine water quality. The application of the General Diatom Index (GDI) revealed significant differences in water quality (p < 0.05) among the Santa Inés stream and the Yacuambi and El Salado rivers. In terms of abundance, individuals from the genera Microspora, Ulothrix, Navicula, Gomphonema, and Ulnaria were recorded. Temperature, dissolved oxygen, and conductivity were the variables that most differentiated the studied rivers (p < 0.05). Multivariate analysis revealed the formation of specific groups for each river, including phytoplankton organisms that serve as indicators of water quality and physicochemical variables, which together explained at least 69 % of the data variability in all cases.